PERBANDINGAN TAFSIR TULIS DAN LISAN M. QURAISH SHIHAB TENTANG QS. AL-QALAM DALAM TAFSIR AL-MISBAH (ANALISIS CIRI KELISANAN ADITIF ALIH-ALIH SUBORDINATIF) - Muhammad Alwi, HS (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This paper would like to present in a comparative analysis the interpretation made by M. Quraish Shihab about QS. al-Qalam. Comparison of interpretations in this paper will elevate the written and oral interpretation of M. Quraish Shihab at once, in this case the interpretation of writing will refer to the Tafseer of Al-Misbah, and the interpretation of the Oral will refer to the